Developing Student Learning Index: Macro-Level Study In Cambodia - Harth, Bunhe; Wongwanich, Suwimon; Piromsombat, Chayut (Scholar: Human Sciences, 2019)
The purpose of this study was to develop student learning index in Cambodia. Two specific objectives were 1) to measurement model of student learning and 2) to measure learning index of Cambodian students. The samples of the study were 1619 high school students selected by using multi-stage random sampling at macro level. The research instrument was a five-point rating scale. Key research findings were summarized as follows: 1). The measurement model of student learning was measured by two components–Learning to Know and Learning to Do. Each component was composed of two sub-components: processes and outcomes of learning. Each sub-component was measured by three indicators. The psychometric properties showed that the instrument had content validity (IOC ranged between .50-1.00), was highly reliable (Cronbach’s α = .83-.94), and had construct validity (χ2 (15, N=1619) = 22.32, p = .10, CFI = 1.00, TLI = .99, SRMSR = .01, RMSEA= .02). 2). The average of Cambodian students’ learning index was .649.